Implementasi Kebijakan tentang Pelaksanaan Pembelajaran Tatap Muka pada Masa Pandemi Covid-19 di Sekolah Luar Biasa Kota Padang - Astri Mitha Nabilah; Adil Mubarak (Policy, Law and Political Research Center, 2022)
The study aims to see the implementation of face-to-face study during the covid-19 pandemic in Padang city. It is a qualitative study using descriptive methods. Research informants are determined by purposive sampling techniques. Where the information consists of provincial education service, Padang city education service, Special school country 1 Padang, Special school ypplb, Special school ypac, Special school al-ishlaah padang. Data collection conducted through interviews, documentation studies and observation. Testing the validity of data using the triangulation technique. Data analysis techniques are done with data reduction, data presentation, data verification. The study shows that implementation of policies on the implementation of suda's face to face learning is implemented according to policy implementation indicators, standards and goals, resources, characteristics of the executive organization, attitudes of the executioners, organizational communications, social, economic, and political environment. But the implementation is still rudimentary because there isa shortage of indicators and there are several inhibitors such as the same rules and the lack of resources. But there is also a contributing factor such as support for student parents, and it can dissever learning loss.